Method of fingerprint and voiceprint based decision level fusion recognition - Jianwu ZHANG; Jiajia YANG; Zhendong WU (Dianxin kexue)
Because of strong complementarity in the recognition environment and the low correlation characteristics of the two features,a fingerprint and voiceprint based decision level fusion recognition method was proposed.After extracting the features and recognition of corresponding fingerprint and voiceprint,the second comparison of choosing model (SCCM) was used to classify at the decision-making level and judge whether to enable voiceprint recognition according to the category,reduced the average data processing volume of the dual-mode fushion system by 32.8%.Experiments applied to FVC2002DB1 fingerprint library and self-collecting voiceprint library.The experimental results show that the multi-biometrics fusion effectively solves the single-modal recognition limitation and the recognition rate improves nearly 5.08% and 4.60% as well as get a more stable system.